The Grand Budapest Hotel [videorecording (DVD)] - Anderson, Wes, 1969-; Guinness, Hugo; Fiennes, Ralph; Abraham, F. Murray; Amalric, Mathieu, 1965-; Brody, Adrien; Dafoe, Willem; Goldblum, Jeff, 1952-; Keitel, Harvey; Law, Jude, 1972-; Murray, Bill, 1950 September 21-; Norton, Edward; et al. (2014)
The adventures of Gustave H, a legendary concierge at a famous European hotel between the wars, and Zero Moustafa, the lobby boy who becomes his most trusted friend. The story involves the theft and recovery of a priceless Renaissance painting and the battle for an enormous family fortune.